2018
DOI: 10.1002/jcp.26426
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles: Intercellular messengers in cutaneous wound healing

Abstract: Longtime considered as inert cellular debris, microvesicles (MVs) have gained tremendous attention in the past decade. MVs are 100-1000 nm vesicles released into the extracellular environment by the outward budding and fission of the plasma membrane. They are now regarded as essential mediators of cell-to-cell interactions in a variety of physiological and pathological processes. In this review, we discuss the increasingly recognized contribution of MVs to the biology of wound healing. We highlight current con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 99 publications
(115 reference statements)
1
36
0
Order By: Relevance
“…However, a great interest has recently arisen for a novel class of cell‐to‐cell messengers known as microvesicles (MVs). It is now accepted that MVs serve as vectors for the intercellular transfer of bioactive molecules during wound healing (Laberge, Arif, & Moulin, ). These small cell‐derived structures (100–1,000 nm in diameter) are released into the extracellular environment by budding of the plasma membrane (Jimenez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a great interest has recently arisen for a novel class of cell‐to‐cell messengers known as microvesicles (MVs). It is now accepted that MVs serve as vectors for the intercellular transfer of bioactive molecules during wound healing (Laberge, Arif, & Moulin, ). These small cell‐derived structures (100–1,000 nm in diameter) are released into the extracellular environment by budding of the plasma membrane (Jimenez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The membrane proteins could also be components of extracellular vesicles, which are increasingly recognized for their ability to modulate the wound healing process. 16 These potential sources of membrane proteins are not mutually exclusive, as apoptotic cell death triggers the release of apoptotic bodies. 17 This and other responses to local tissue injury (e.g., cell activation in the vicinity of an injury 18 ) are likely to be more prominent in MSTCs or minced tissue, due to the higher total wound edge area compared with larger conventional grafts (since the wound area scales with the circumference of the tissue samples, for this study the total wound area was about 20 • lower in the 10 mm-diameter intact skin, compared with an equivalent volume of 0.5 mm-diameter MSTCs), which is likely to at least partially account for the observed differences in protein release profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In normal cellular physiology, EVs are now appreciated as important messengers in orchestrating immune responses during processes, such as wound repair and infection with foreign organism (Laberge et al, 2018;Robbins and Morelli, 2014). Early work in the field revealed that immune cells utilize EVs, particularly exosomes, to mediate antigen presentation with other cells at a systemic level (Raposo et al, 1996;Wolfers et al, 2001;Zitvogel et al, 1998).…”
Section: Extracellular Vesicles As Vehicles Of Immune Evasionmentioning
confidence: 99%